PENERAPAN MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI TEKANAN KELAS VIII SMP NEGERI 7 TAMBANG - Siskawati, Ernita; Azizahwati, Azizahwati; Syaflita, Dina (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
This study aims to determine the increase in cognitive learning outcomes of class VIII students on pressure material at SMP Negeri 7 Tambang using the Children Learning In Science (CLIS) model. The samples in this study were two classes, namely class VIII-A as the control class and class VIII-B as the experimental class. The type of research used is Experimental Research with a posttest-only control design model. Data collection was carried out using a written test instrument in the form of multiple choice questions of 20 items. The data obtained is then subjected to a normality test and homogeneity test to find out whether the data obtained is homogeneous or not. Furthermore, to find out whether or not there were significant differences in learning outcomes between the experimental and control classes, an independent sample test was carried out with a significance level of 0.05. Based on the results of data processing, a significance <0.05 was obtained which indicated that Ho was rejected and Ha was accepted. it can be concluded that there are significant differences in students' cognitive learning outcomes between classes that use the CLIS model and classes that apply conventional learning models.